2021
DOI: 10.1017/s0007114521001483
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of overweight/obesity-related lifestyles in university students: Results from the EHU12/24 study

Abstract: This paper investigates the prevalence and interaction of overweight/obesity-related lifestyles (specifically, examining whether subjects meet the recommended criteria), in a representative sample of university students. This study is part of the project EHU12/24, an observational cross-sectional study, designed to assess the prevalence of excess body fat (BF) and major risk of developing overweight/obesity, according to a standardised protocol. In a cohort of 603 students, aged between 18 and 28 years, of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 74 publications
1
17
1
2
Order By: Relevance
“…Although the direct comparison of our results to those of other studies is rather difficult given the data-driven nature of such analysis, high-fat and high-sugar foods have previously been connected to obesity in students [ 46 , 64 , 65 ] and young adults [ 66 ]. High alcohol intake has also been associated with obesity in other studies, including university students [ 63 ] but not all [ 46 ]. The documented correlation of a high protein pattern with obesity is in line with the previously reported metabolic risks of this pattern [ 57 ].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the direct comparison of our results to those of other studies is rather difficult given the data-driven nature of such analysis, high-fat and high-sugar foods have previously been connected to obesity in students [ 46 , 64 , 65 ] and young adults [ 66 ]. High alcohol intake has also been associated with obesity in other studies, including university students [ 63 ] but not all [ 46 ]. The documented correlation of a high protein pattern with obesity is in line with the previously reported metabolic risks of this pattern [ 57 ].…”
Section: Discussionmentioning
confidence: 97%
“…However, direct within-study comparisons have shown a higher Mediterranean diet adherence of Dutch students than Greeks [ 18 ]. Some studies have shown no association of the Mediterranean diet to anthropometric indices [ 53 ], while others have shown inverse relationships between obesity and Mediterranean Diet adherence [ 63 ]. In our study, there was no linear relationship between the Mediterranean diet and BMI in multi-adjusted linear regression, but an inverse monotonic relationship was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skipping breakfast is common in university students [27]. The prevalence of skipping breakfast in university students was 32%, 9-16%, 33%, 46-69%, and 17-31% in the US [28], Spain [29,30], Australia [31], China [32,33], and Japan [34,35], respectively. Some studies reported that skipping breakfast was associated with healthcompromising behaviors, such as smoking or alcohol drinking [36], in addition to affecting test grades and school attendance [37].…”
Section: Introductionmentioning
confidence: 99%